Political booms local money and power in Taiwan, East China, Thailand, and the Philippines - White, Lynn T.; iGLibrary (online resource). (Singapore World Scientific Publishing Co. Pte. Ltd., 2009)
Why have Taiwan, rich parts of China, and Thailand boomed famously, while the Philippines has long remained stagnant both economically and politically? Do booms abet democracy? Does the rise of middle "classes" promise future liberalization? Why has Philippine democracy brought no boom and barely served the Filipino people?
Political booms : local money and power in Taiwan, East China, Thailand, and the Philippines -- Contents -- Abbreviations -- Romanizations -- Acknowledgements -- Chapter 1: Introduction: What Politics Aids Booms? -- Chapter 2: Political Roots of Taiwans Boom -- Chapter 3: Political Roots of East Chinas Boom -- Chapter 4: Political Roots of Thailands Boom -- Chapter 5: Political Roots of Philippine Stasis -- Chapter 6: Political Results of Taiwans Boom -- Chapter 7: Political Results of East Chinas Boom -- Chapter 8: Political Results of Thailands Boom -- Chapter 9: Political Results of Philippine Stasis -- Chapter 10: Conclusion: Do Booms Aid Democracy? -- Sources -- Name Index -- Subject Index.
Includes bibliographical references and index.
Electronic Reproduction.
Keywords: Power (Social sciences) -- Asia; Democracy -- Asia; Political corruption -- Asia; Television -- Psychological aspects -- Philippines; Electronic books; Asia -- Politics and government -- 1945-.; Asia -- Economic conditions -- 1945-.